2003
DOI: 10.1126/science.1078020
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Naphthalene Dioxygenase: Side-on Binding of Dioxygen to Iron

Abstract: Binding of oxygen to iron is exploited in several biological and chemical processes. Although computational and spectroscopic results have suggested side-on binding, only end-on binding of oxygen to iron has been observed in crystal structures. We have determined structures of naphthalene dioxygenase that show a molecular oxygen species bound to the mononuclear iron in a side-on fashion. In a complex with substrate and dioxygen, the dioxygen molecule is lined up for an attack on the double bond of the aromatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

34
484
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 517 publications
(522 citation statements)
references
References 25 publications
(16 reference statements)
34
484
1
3
Order By: Relevance
“…The observation of dioxygen molecules near enzyme active sites is precedented in other structures (10,11). Dioxygen is associated with metal atoms in naphthalene dioxygenase and cytochromes P450 (10,12). The proposed dioxygen in this FMO structure is bound to Asn-91.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of dioxygen molecules near enzyme active sites is precedented in other structures (10,11). Dioxygen is associated with metal atoms in naphthalene dioxygenase and cytochromes P450 (10,12). The proposed dioxygen in this FMO structure is bound to Asn-91.…”
Section: Discussionmentioning
confidence: 99%
“…[19] This implies that the BDEOH of the [Fe IV (O)(Por +• )] + system will be considerably smaller than that of P450 CpdI and unable to react via hydrogen atom abstraction. Indeed, we calculate a BDEOH for the reaction of 3 [Fe III (OH)(Por +• )] + into CpdI and a hydrogen atom of DE+ZPE = 66.3 kcal mol -1 , whereas for a P450 CpdI model a value of 88.9 kcal mol -1 was obtained. [20] In aliphatic hydroxylation the energy of the hydrogen atom abstraction step is equal to the difference in BDECH of the substrate and the BDEOH of the oxidant.…”
Section: Theorymentioning
confidence: 99%
“…[2] Highly relevant for environmental purposes are, for instance, the naphthalene dioxygenases that have functions in biotechnology that include the cleaning up of oil-spills and removal of aromatic compounds from soil. [3] Also, in the human body applications of heme and nonheme iron dioxygenases are found, for instance, for the biodegradation of aromatic amino acids starting with a mono-or dihydroxylation reaction. [4] Further arene activating enzymes in the body include the thiolate-ligated heme mono-oxygenases called cytochromes P450 (P450) that have been shown to hydroxylate arenes to phenols as a means to metabolize drugs as well as xenobiotic molecules in the liver.…”
Section: Introductionmentioning
confidence: 99%
“…First, X-ray crystallography has revealed that NDO forms a side-on bound Fe (III)-hydroperoxy substrate intermediate at the mononuclear iron site. 6 Second, the STO experiments have shown that the chemical reaction can be carried out without NDR and NDF. Both metal centers of NDO are oxidized during the STO revealing the sources of the two reducing equivalents required by the stoichiometry of the reaction.…”
mentioning
confidence: 99%